Unassisted self-healing photocatalysts based on Le Chatelier’s principle - Aito Takeuchi; Yoshitaka Kumabe; Takashi Tachikawa (Communications Chemistry)
Abstract Self-healing is a fundamental ability inherent in humans, plants, and other living organisms. To date, a variety of materials with self-healing properties have been developed. However, these materials usually require external inputs such as electric potentials or healing agents to initiate or promote self-healing reactions. Herein, we present a novel self-healing mechanism that operates without any external input, utilizing the dynamic equilibrium between the solid-state and dissolved materials. We employed organic–inorganic perovskites to validate our strategy. Single-particle spectroscopy and imaging demonstrated the spontaneous self-healing of perovskites after photodamage under dynamic equilibrium conditions. Furthermore, we found that perovskites can generate hydrogen in both healed and damaged states. Remarkably, the perovskites exhibited hydrogen generation over four cycles of photodamage and self-healing. The proposed concept and experimental results provide valuable insights for the development of energy conversion and storage systems with improved long-term durability.